Being (past and present) President of the ERS: interview about the role, perspectives on career development, and vision for the Society. Issue 2 (12th July 2022) - Siciliano, Matteo; Schiavi, Enrico; Cullivan, Sarah; Bradicich, Matteo; Lichtblau, Mona; Cruz, Joana
For this article, we invited early career members (ECMs) to interview the past and current Presidents of the European Respiratory Society (ERS), Professor Anita Simonds and Professor Marc Humbert, to share their motivations for becoming ERS President, experiences and goals during their presidency, perspectives on career development, visions for the society, and future challenges and opportunities in the respiratory field in the coming years. During the interviews, they provided important messages to help ECMs build their own successful career. We challenge ECMs to read the interviews and get inspired! This article presents the views of the past and current Presidents of the ERS regarding their role, perspectives on career development and vision for the Society, along with important messages to inspire ECMs to build their own successful career. https://bit.ly/3kAvxIM